2016
DOI: 10.1177/1756287216675778
|View full text |Cite
|
Sign up to set email alerts
|

The link between vascular dysfunction, bladder ischemia, and aging bladder dysfunction

Abstract: Abstract:The vascular supply to the human bladder is derived mainly from the superior and inferior vesical arteries, the latter being directly connected to the internal iliac artery. Aging is associated with an impairment of blood vessel function and changes may occur in the vasculature at the molecular, cellular and functional level. Pelvic arterial insufficiency may play an important role in the development of bladder dysfunctions such as detrusor overactivity (DO) and the overactive bladder syndrome. Chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
94
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 138 publications
1
94
0
7
Order By: Relevance
“…; Andersson et al . ). The beneficial effects of α‐adrenoceptor antagonists, β3‐adrenoceptor agonists or PDE5 inhibitors on bladder storage symptoms may be attributed to an improvement of the bladder microcirculation.…”
Section: Discussionmentioning
confidence: 97%
“…; Andersson et al . ). The beneficial effects of α‐adrenoceptor antagonists, β3‐adrenoceptor agonists or PDE5 inhibitors on bladder storage symptoms may be attributed to an improvement of the bladder microcirculation.…”
Section: Discussionmentioning
confidence: 97%
“…However, prolonged or chronic ischemia may overwhelm this mechanism and, overtime, progresses to the detrusor overactivity and ultimately to detrusor underactivity observed in diseases of chronic ischemia. 2,23 We propose that this present study may characterize an initial acute stage in the spectrum of progression to DU.…”
Section: Discussionmentioning
confidence: 84%
“…Nearly 50% of men and women undergoing urodynamics for lower urinary tract symptoms (LUTS) have been found to have detrusor underactivity, with increasing prevalence associated with increasing age . Chronic ischemia is a recognized risk factor in the pathophysiology of this disease process in the pre‐clinical and clinical settings . Decreased bladder perfusion is known to occur at higher fill volumes or pressures, but whether repetitive cyclic episodes of relative ischemia can lead to the pathophysiology of UAB remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At a rat study, Saito et al reported that bladder blood flow was significantly lower in older rats compared with the younger rats. Vascular stiffness increased and vascular compliance decreased with aging . These morphological changes may also cause vascular insufficiency and lead to organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%